Designing an O2‐Insensitive Glucose Oxidase for Improved Electrochemical Applications. Issue 10 (10th August 2017) - Tremey, Emilie; Stines‐Chaumeil, Claire; Gounel, Sébastien; Mano, Nicolas
Abstract: The O2 reactivity of flavoproteins and particularly, glucose oxidase, is a limitation for numerous biotechnological applications, and this has been the subject of intense research. In the present study, we performed site‐directed mutations on Val464 of GOx from Penicilium amagasakiense and combined steady‐state, rapid kinetics and electrochemistry to investigate the effect of such mutations on the O2 reactivity. We propose that replacing the non‐polar Valine with a polar Serine permits to decrease the diffusion/stabilization of O2 near the active redox center without altering the oxidation of glucose. When incorporated in osmium hydrogels, the resulting electrodes were insensitive to O2 in the 0.5–60 mM glucose concentration range and were 4.7 times more stable under continuous operation than similar electrodes made with the native GOx. To the best of our knowledge, this is the first example in which O2 sensitivity in GOx can be significantly decrease without altering the electrochemical efficiency for glucose oxidation. Abstract : Mutant mediator : Site‐directed mutations on position V464 and combined steady‐state, rapid kinetics, and electrochemistry are performed to investigate the effect of such mutations on O2 reactivity. With the objective to decrease the O2 sensitivity of GOx, the most promising mutant is further combined with K424E, which is known to improve the rate of electron transfer between osmium redox polymers and GOx.